Entrepreneurial attitudes: A distinction between two professional groups - R. Van Wyk; A. B. Boshoff (South African Journal of Business Management, 2004)
This study investigates discrimant ability of the Entrepreneurial Attitude Orientations Scale of 365 individuals practicing in two mutually exclusive professions (pharmacists N = 200 and accountants N = 175) on the profiles of Holland's hexagon of occupational groups. Anova was performed with the EAOS sub-and total scales as dependent variables and entrepreneurial and non-entrepreneurial profiles as independent variables. Some discriminance by means of Tukey's Range Test and interaction through LS-means was found between the two professions and employment status of individuals. Implications for management are indicated.
Keywords: 650